2021
DOI: 10.3390/ma14174901
|View full text |Cite
|
Sign up to set email alerts
|

Work Hardening of Heat-Treated AlSi10Mg Alloy Manufactured by Selective Laser Melting: Effects of Layer Thickness and Hatch Spacing

Abstract: The present study analyzed the microstructure and the mechanical properties of AlSi10Mg SLMed bars (10 × 10 × 300 mm) and billets (10 × 100 × 300 mm) before and after the direct aging at 200 °C for 4 h and the T6 heat treatment. The discussed results are compared to those obtained by the AlSi10Mg samples manufactured with the same geometry but using different process parameters (layer thickness higher than 40 μm and a hatch spacing lower than 100 μm) and also through the Quality Index (QI). These work conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 79 publications
3
22
1
Order By: Relevance
“…The principal process parameters ( P , v , h , t ), which define the ED function (Equation (1)), influence microstructure and mechanical properties of AlSi10Mg and Ti6Al4V as-built samples manufactured via L-PBF process [ 9 , 14 , 68 ]. As shown in Figure 4 , they are the only parameters that can be fully controlled, together with the laser source parameters, to obtain a high-quality sample.…”
Section: Laser-powder Bed Fusion (L-pbf) Processmentioning
confidence: 99%
See 4 more Smart Citations
“…The principal process parameters ( P , v , h , t ), which define the ED function (Equation (1)), influence microstructure and mechanical properties of AlSi10Mg and Ti6Al4V as-built samples manufactured via L-PBF process [ 9 , 14 , 68 ]. As shown in Figure 4 , they are the only parameters that can be fully controlled, together with the laser source parameters, to obtain a high-quality sample.…”
Section: Laser-powder Bed Fusion (L-pbf) Processmentioning
confidence: 99%
“…Shi et al [ 128 ] showed an increase of layer thickness up to 200 μm, maintaining a Ti6Al4V sample density δ > 99.73% (fully dense). On the other hand, varying the layer thickness of AlSi10Mg and Ti6Al4V samples manufactured via L-PBF changes the mechanical properties obtained [ 9 , 32 , 103 , 128 ]. The use of double or quadruple lasers, which work in parallel on the same layer powder bed, or the use of skin-core scan strategy are other examples concerning the increase in the BR [ 120 , 129 ].…”
Section: Laser-powder Bed Fusion (L-pbf) Processmentioning
confidence: 99%
See 3 more Smart Citations